Diagnostic Accuracy of Robot-Guided, Software Based Transperineal MRI/TRUS Fusion Biopsy of the Prostate in a High Risk Population of Previously Biopsy Negative Men. (21st November 2016) - Kroenig, Malte; Schaal, Kathrin; Benndorf, Matthias; Soschynski, Martin; Lenz, Philipp; Krauss, Tobias; Drendel, Vanessa; Kayser, Gian; Kurz, Philipp; Werner, Martin; Wetterauer, Ulrich; Schultze-Seemann, Wolfgang; et al.
Abstract : Objective . In this study, we compared prostate cancer detection rates between MRI-TRUS fusion targeted and systematic biopsies using a robot-guided, software based transperineal approach. Methods and Patients . 52 patients received a MRIT/TRUS fusion followed by a systematic volume adapted biopsy using the same robot-guided transperineal approach. The primary outcome was the detection rate of clinically significant disease (Gleason grade ≥ 4). Secondary outcomes were detection rate of all cancers, sampling efficiency and utility, and serious adverse event rate. Patients received no antibiotic prophylaxis. Results . From 52 patients, 519 targeted biopsies from 135 lesions and 1561 random biopsies were generated (total n = 2080 ). Overall detection rate of clinically significant PCa was 44.2% (23/52) and 50.0% (26/52) for target and random biopsy, respectively. Sampling efficiency as the median number of cores needed to detect clinically significant prostate cancer was 9 for target (IQR: 6–14.0) and 32 (IQR: 24–32) for random biopsy. The utility as the number of additionally detected clinically significant PCa cases by either strategy was 0% (0/52) for target and 3.9% (2/52) for random biopsy. Conclusions . MRI/TRUS fusion based target biopsy did not show an advantage in the overall detection rate of clinically significant prostate cancer.